Effect of changing flow rate on habitat suitability of tinfoil barb in upstream Langat River using CASiMiR model - Tavakkoli, Tannaz; Nowrouzi, Majid; Mohammad, Thamer Ahmad (Universiti Putra Malaysia, 2012)
The habitat suitability of freshwater species and ecosystems should also be considered in every attempts made to manage water to meet human requirements. River hydraulics and geometry has direct effect on habitat suitability in rivers and fish is used as a measure for this suitability. CASiMiR model (Computer Aided Simulation Model for Instream Flow Regulations) is a new model which is proposed to be used to assess suitability of rivers habitat. In this study, CASiMiR model is used to assess the habitat suitability for Langat River, Selangor, Malaysia by taking one stretch of 200 m at upstream. Fuzzy models were developed by an experienced fish expert for the selected fish species which called Tinfoil Barb in its two different life stages (adult and juvenile). Two indices were used to assess the habitat suitability and these are Weighted Usable Area (WUA) and Hydraulic Habitat Suitability (HHS).The current study on habitat modelling was the first time applying in Malaysia and the model analysed the relationship between flow rate and physical habitat as defined by the combination of depths, velocities and substrates found in the selected reach of Langat river. Therefore additional factors influencing habitat conditions such as geomorphological changes, seasonal changes in aquatic vegetation, water quality and temperature were not investigated within this study. Based on the computed indices, the highest habitat suitability for adult of Tinfoil Barb was found at high flow rate of 10.65 m3/s at upstream indicating almost good habitat suitability for this life stage which increases when the flow rate increase during the year. On contrary and for juvenile life stage, the habitat suitability was found in low flow rate of 1.3 m3/s. Juvenile benefits more when the flow rate is low.